Acceptance of the vaccine against human papilloma virus in parents of primary girls. Huánuco, 2017 - Munguia-Daza, Francis (2019)
Objective: To determine the existence of a relationship between knowledge, attitude and perception of benefit on the acceptance of the vaccine against the human papilloma virus of the parents of girls of the 5th year of primary school. Methods: Descriptive cross-sectional, analytical design, consisting of 93 parents. The relationship between knowledge, attitude and psychological factor on the acceptance of the vaccine against the human papillomavirus is described, for which the Likert scale was used for attitude. It was evaluated by chi squared, for the study variables, SPSS.V15 was used. Results: It was found that 82.8% of the parents were female. The level of adequate knowledge of the parents was 77.42%, with a predominance of the indifferent attitude 55.9%, with a perception of positive benefit of 81.7%. A significant relationship was found between the level of knowledge p = 0.001 RR = 0.680 [IC95%: 0.400-0.924], attitude p = 0.002, orientation p = 0.029 RR = 1.27 [IC95%: 1.016-1.588] with the Acceptance of the vaccine against the human papillomavirus. Conclusion: Most of the parents surveyed know about the vaccine against the Human Papillomavirus, its effectiveness, its importance, the adverse effects and the doses of the vaccine. Finally, there is a relationship between knowledge, attitude and orientation regarding the acceptance of the vaccine against human papillomavirus.